Expression of Vibrio salmonicida virulence genes and immune response parameters in experimentally challenged Atlantic salmon (Salmo salar L.) - Bjelland, Ane M.; Fauske, Aud Kari; Nguyen, Anh; Orlien, Ingvild E.; Østgaard, Ingrid; Sørum, Henning (Frontiers in Microbiology, 2013)
The Gram-negative bacterium Vibrio salmonicida is the causative agent of cold-water vibriosis (CV), a hemorrhagic septicemia that primarily affects farmed Atlantic salmon (Salmo salar L.). The mechanisms of disease development, host specificity and adaptation, as well as the immunogenic properties of V. salmonicida are largely unknown. Therefore, to gain more knowledge on the pathogenesis of CV, 90 Atlantic salmon parr were injected intraperitonellay with 6 x 106 CFU of V. salmonicida LFI1238. Samples from blood and spleen tissue were taken at different time points throughout the challenge for gene expression analysis by two-step reverse transcription quantitative real-time polymerase chain reaction. Out of a panel of six housekeeping genes, accD, gapA and 16S rDNA were found to be the most suitable references for expression analysis in Vibrio salmonicida. The bacterial proliferation during challenge was monitored based on the expression of the 16S rRNA encoding gene. Before day 4, the concentrations of V. salmonicida in blood and spleen tissue demonstrated a lag phase. From day 4, the bacterial proliferation was exponential. The expression profiles of eight genes encoding potential virulence factors of V. salmonicida were studied. Surprisingly, all tested virulence genes were generally highest expressed in broth cultures compared to the in vivo samples. We hypothesize that this general muting of gene expression in vivo may be a strategy for V. salmonicida to hide from the host immune system. To further investigate this hypothesis, the expression profiles of eight genes encoding innate immune factors were analyzed. The results demonstrated a strong and rapid, but short-lasting innate immune response against V. salmonicida. These results suggest that the bacterium possesses mechanisms that inhibit and/or resist the salmon innate immune system until the host becomes exhausted of fighting the on-going and eventually overwhelming infection.